EDUKASI LITERASI KEUANGAN BAGI PELAKU USAHA MIKRO KECIL MENENGAH (UMKM) KOTA MAGELANG GUNA MENINGKATKAN KESEJAHTERAAN EKONOMI - Retnosari, Retnosari; Togar Laut, Lorentino; Sarwanti, Sri (Yayasan Nusantara Hasana Berdikari, 2025)
MSMEs in Magelang City play a vital role in driving local economic growth and creating jobs for the community. However, one of the main challenges faced by business owners in this area is the low level of understanding and implementation of proper bookkeeping systems. Many MSMEs in Magelang City still maintain unstructured manual records, and most of them lack any financial records at all. Therefore, activities to be carried out include financial literacy education and training, as MSMEs in Magelang City require a better understanding of the importance of proper bookkeeping, from preparing simple financial reports to accurately recording cash flow. This training will help them manage their business finances more efficiently and in a structured manner. The purpose of this community service program is to improve MSME owners' understanding of the basic concepts of financial literacy, such as financial record keeping, cash flow management, and financial planning. Furthermore, this community service program is expected to provide training on access to formal financing, including banking through People's Business Credit (KUR).